PENGARUH PENDAMPINGAN SOSIAL DAN PARTISIPASI MASYARAKAT TERHADAP KEBERHASILAN PROGRAM REHABILITASI SOSIAL RUMAH TIDAK LAYAK HUNI (RS-RTLH) DI DESA TAPOS KECAMATAN CADASARI KABUPATEN PANDEGLANG - Irmayanti Irmayanti (LPPM STIA Banten, 2021)
The Effect of Social Assistance and Community Participation on the Success of the Social Rehabilitation Program for Uninhabitable Houses (RS-RTLH) in Tapos Village, Cadasari District, Pandeglang Regency. The method used is a quantitative method with an associative correlational approach, and literature study to sharpen problem solving. From the calculation results, it is obtained that the value of r is 0.504. This shows that the implementation of the Social Assistance Program has a positive relationship. Meanwhile, the coefficient of determination (KD) can influence the implementation of the Social Assistance Program by 25.40%. The remaining 74.60% is influenced by other factors not examined. While the effect of Community Participation in Program Implementation obtained an r value of 0.407, this indicates that Community Participation has a strong and positive relationship to Program Implementation. The coefficient of determination (KD) Community participation can influence program implementation by 16:56%. The remaining 83.44% is influenced by other factors not examined. While the R2 (R Square) value is 0280 with an Fcount value of 12,030 while an F table with a significance level of 5% is obtained by the degree of numerator k = 2 and df = nk-1 = 65-2-1 = 62, obtained by a Ftable value of 3,145. The results of Fcount (12.030) > Ftable (3.145), thus Ha is accepted and Ho is rejected. Thus variable X1 (Social Assistance) and Variable X2 Community Participation together have a significant effect on variable Y (Program Implementation).